Lithocholic acid attenuates DON-induced inflammatory responses via epigenetic regulation of DUSP5 and TRAF5 in porcine intestinal epithelial cells - Wang, Shiqi; Peng, Xiaoxu; Zhu, Qi; Lu, Sichen; Hu, Ping; Kim, In Ho; Liu, Hao-Yu; Ennab, Wael; Muniyappan, Madesh; Cai, Demin (Frontiers in Veterinary Science, 2025)
Deoxynivalenol (DON) is the most common mycotoxin that frequently contaminates human food and animal feed, resulting in intestinal diseases and systemic immunosuppression. Lithocholic acid (LCA) exhibits various pharmacological activities. RNA-seq and ChIP-qPCR analysis were used in the current study to investigate the protective mechanism of LCA for DON-induced inflammatory Responses via Epigenetic Regulation of DUSP5 and TRAF5 in porcine ileal epithelial cell lines (IPI-2I) cells. The IPI-2I cells were treated with the vehicle group, 250 ng/mL DON, 20 μmol/L LCA, 250 ng/mL DON+ 20 μmol/L LCA for 24 h could induce inflammatory Responses via Epigenetic Regulation of DUSP5 and TRAF5 in IPI-2I cells. By analyzing the transcriptional profiles of DON and LCA-treated IPI-2I, we observed significant transcriptional changes in IPI-2I cells. Further analysis of up-and down-regulated differential genes revealed the enrichment of pathways closely related to inflammation and apoptosis, such as the MAPK signaling pathway, IL17 signaling pathway, and Wnt signaling pathway. An upregulated (p < 0.05) relative mRNA expression level of RAP1B, GDNF, FGF2, IL1R1, RAPGEF2, DUSP5, TGFB3, CACNA1G, TEK and RPS6KA2 were noted in IPI-2I exposed to DON. DON-exposed IPI-2I cells dramatically enhanced (p < 0.05) histone marks associated with transcriptional activation, H3K9ac, H3K18ac, H3K27ac, H3K4me1, H3K9bhb, H3K18bhb Pol-II and Ser5 Pol-II at the enhancers of DUSP5 and TRAF5. Overall, our findings provide a theoretical basis for understanding the mechanism of action of LCA in attenuating DON-induced intestinal injury and for better understanding the potential of LCA as a treatment or prevention of mycotoxin-associated intestinal diseases in swine production.